Perspectives of Usak University faculty of medicine and dentistry students to biochemistry course (Annals of Medical Research, 2021)
Aim: In this study, we aimed to share our experiences about patients with miscellaneous non-specific malign stromal tumors of testis. We report the demographic and clinical characteristics and the long-term results in patients with non-specific malign stromal tumors of testis.Material and Methods: 234 patients with testicular cancer between June 1994 and January 2019 have been evaluated retrospectively. Eleven patients (Dedifferentiated liposarcoma, Diffuse large B-cell lymphoma, Embryonal rhabdomyosarcoma, Adenocarcinoma of the epididymis, Ewing’s sarcoma of the testis, Testicular leiomyosarcoma, Well-differentiated liposarcoma, Paratesticular high grade sarcoma and Paratesticular malignant mesothelioma) whose data were reached, are taken into the study. Patients’ age, scrotal localization of symptoms, clinical examination findings, serum tumor marker levels, pathology results and follow-up period were recorded. Results:The mean age at diagnosis was 43.7 years (range, 18 to 79). 54.5% of the lesions were localized to the right hemiscrotal area and of 45.4% to the left hemiscrotal area. None of patients had a history of unilateral undescended testis in medical history or testicular cancer in familial history. Serum tumor markers were normal in all patients. The mean scrotal mass lesion at diagnosis was 59.9 mm3 (range, 33 to 138 mm3). 3 or 4 cyles of chemotherapy protocols were administered in necessary cases. Mean follow-up period was 80.6 months (range, 12 to 297 months). Tumor recurrence was occured in only two patients (Dedifferentiated liposarcoma and Adenocarcinoma of the epididymis) during the follow-up.Conclusion: Miscellaneous non-specific malign stromal tumors of the testis should be kept in mind especially in middle age group patients presented with malign scrotal lesions. Surgical treatment should be aggressive and additional specific treatment according to pathology result should be planned without delay. Follow-up protocols are recommended to be tumor specific.
Keywords: Non-specific malign stromal tumors; testicular cancer; testis tumors.